Optimalisasi Pesan Moderasi Beragama di Era Digital: Studi Website NU Online - Muhammad Fanshoby; Khofifah Nur Hidayat (Dakwah Institut PTIQ Jakarta, 2024)
This research focuses on optimizing religious moderation messages through Search Engine Optimization (SEO) on NU Online, an Islamic website platform in Indonesia. Using a constructivist paradigm with a descriptive qualitative approach, this study explores how religious moderation messages are constructed and disseminated through Computer-Mediated Communication (CMC) and SEO. Data was collected through interviews, observations, and documentation, with a specific analysis on the popular article titled